Dinamika Tipologi Kajian Skripsi Mahasiswa Prodi Pendidikan Bahasa Arab FKIP Universitas Jambi 2019-2023 - Muid, Abdul; Mustofa, Ady Muh. Zainul (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2023)
This research departs from academic anxiety, the thesis is only used as an annual ritual for student graduation requirements, without paying attention to competency standards, methodology, and actuality of issues regarding the world of education, especially Arabic is ignored. In this case, the thesis of the student of the Arabic Language Education Study Program of Jambi University in 2019-2023. Some of the questions that will be answered in this study are: what are the Arabic language education clusters that have been studied; what is the percentage, which clusters are saturated and need to be abandoned to avoid recurrence; What clusters are still open to be used as topics of study in the future; How is its adaptability to new educational problems that are currently in society. This research is literary, because the data and primary sources come from written materials derived from the 2019-2033 PBA University Jambi University student thesis. This research is descriptive qualitative, data collection using documentation techniques. Written data collected and categorized are then analyzed inductively with content analysis methods. Data analysis techniques are interactive analysis models, namely: data reduction, data submission, and conclusions. The results showed that from 98 thesis, Typology data for the overall study of PBA University Jambi University 2019-2023 student theses, 72 normative studies (73.47%), and 16 pieces of sociology of education or (16.33%). For the actuality of the issue, students of PBA FKIP Study Program of Jambi University are about the issue of applying methods and approaches in learning Arabic. Meanwhile, issues related to contemporary issues regarding Arabic language education, such as translation, content analysis, and character thinking, have not been raised much.